If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + 72)(x + -1) = 0 Reorder the terms: (72 + 3x)(x + -1) = 0 Reorder the terms: (72 + 3x)(-1 + x) = 0 Multiply (72 + 3x) * (-1 + x) (72(-1 + x) + 3x * (-1 + x)) = 0 ((-1 * 72 + x * 72) + 3x * (-1 + x)) = 0 ((-72 + 72x) + 3x * (-1 + x)) = 0 (-72 + 72x + (-1 * 3x + x * 3x)) = 0 (-72 + 72x + (-3x + 3x2)) = 0 Combine like terms: 72x + -3x = 69x (-72 + 69x + 3x2) = 0 Solving -72 + 69x + 3x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '3'. 3(-24 + 23x + x2) = 0 Factor a trinomial. 3((-24 + -1x)(1 + -1x)) = 0 Ignore the factor 3.Subproblem 1
Set the factor '(-24 + -1x)' equal to zero and attempt to solve: Simplifying -24 + -1x = 0 Solving -24 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '24' to each side of the equation. -24 + 24 + -1x = 0 + 24 Combine like terms: -24 + 24 = 0 0 + -1x = 0 + 24 -1x = 0 + 24 Combine like terms: 0 + 24 = 24 -1x = 24 Divide each side by '-1'. x = -24 Simplifying x = -24Subproblem 2
Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1Solution
x = {-24, 1}
| 5x=x+26 | | 12h-18=(4h-6) | | 12x-60=0 | | 6(4y-1)=5 | | 2(x+5)=8 | | 3-n=33 | | x-6=(x-4)1/2 | | y=1.5(1) | | V=dt | | 4x^2-8=20 | | 0=1.5x | | 10(-10x+1)= | | 9n^2-50n-80=0 | | -2a+3(4-a)=-3(a+4)-6 | | V=IxR | | 0.4x^3+0.6x^3-0.3x^3= | | x^2+x+20=0 | | -4m=-32 | | x-7=-20 | | 4x-7x(5x-8)=x-8 | | y=-2(1) | | -4(2z+5)=4 | | 5x+9=11+4x | | j-17=2j+13 | | 5x=3x-18 | | n-3n=14-4 | | d-4d=d+1-4d | | .2x-y=2 | | -18y=9 | | 4x^2y-16xy^2= | | .2-y=2 | | 6(z-1)-5(z+1)=8(z+1) |